The Cratylus : Plato's critique of naming - Baxter, Timothy M. S., 1964-. (Philosophia Antiqua, 1992)
The Cratylus has puzzled many readers with its lengthy discussion of the 'true meanings' of more than a hundred Greek names. This book aims to give a coherent interpretation of the whole dialogue, paying particular attention to these etymologies. The book discusses the rival theories of naming offered by Cratylus, Hermogenes, and Socrates, arguing that Socrates presents a prescriptive theory, laying down what names should be, rather than describing what they are. This distinction between prescriptive and descriptive theories is elaborated and used to illuminate the etymologies themselves. After discussing possible sources for the etymologies, the author argues that the etymological section amounts to a Platonic critique of the muddled attitude of Greek poets and thinkers towards names.